Web-based car parking slot monitoring system - Ch'ng, Shu Fen (2019)
As town modernisation progress, the number of vehicles increases rapidly. Parking is a major problem especially in densely populated areas. Normally, places such as function hall, university, multiplexes and large industries, we need to search for the line that is empty to park our vehicle. Most of the car parking system face problems like wastage of fuel. This also caused us to consume a lot of time finding one car parking slot. To overcome this difficulty, there is need of an advanced car parking slot monitoring system. Thus, a more advanced car parking system is needed to monitor the empty slot of car parking. This carpark slot monitoring system can reduce the time taken used to find the available space by using microcontroller and Infrared sensors (IR) installed at each of the parking slot. The microcontroller serves as a programming tool to run the whole operation, and to make it a system that can meet market needs.